INISIASI PEMBENTUKAN KAWASAN BEBAS ASAP ROKOK DAN TUBERKULOSIS DI RT.08 KELURAHAN BELIUNG, KECAMATAN ALAM BARAJO, KOTA JAMBI - Nasution, Helmi Suryani; Reskiaddin, La Ode; Sari, Puspita; Lanita, Usi (Jurnal Salam Sehat Masyarakat (JSSM), 2024)
Smoking and tuberculosis (TB) are still health problems in Indonesia, Jambi Province and Jambi Municipality. Smoking is a risk factor for TB. Activities to eradicate smoking and TB need to be carried out in RT.08, Beliung Subdistrict, and need to be carried out taking into account the wishes of the chairman of RT.08, Beliung Subdistrict, to establish a Smoke-Free Zone (KTR) in that area. The solution offered is to create a smoke and TB free area. The aim is reducing the impact of smoking on public health and increasing the finding of TB cases through community-based activities. Community service activities that have been carried out include discussions with residents regarding planned activities to be carried out, outreach and education regarding KTR and TB, and declaring smoke and TB free. Activities to establish a smoke-free and tuberculosis-free area in RT 08 Beliung Village have been carried out well. This is indicated by support from various parties and the participation of residents in activities. There needs to be monitored and evaluated by related parties to ensure that RT 08 Beliung Village is truly free from cigarette smoke and TB.